Effects of thymoquinone supplementation on cyclophosphamide toxicity of mouse embryo in vitro - Abdul Rahman, Suzanah; Kamarzaman, Saheera; Abdul Wahab, Azantee Yazmie (IDOSI Publications, 2014)
Thymoquinone is the major active component derived from the traditional medicinal plant Nigella sativa, which has been shown to exhibit antioxidant property through different mechanisms in animal models. This study evaluates the prophylactic effect of thymoquinone supplementation on culture medium to ameliorate cyclophosphamide-induced alterations in cellular differentiation and proliferation during embryo development in vitro. Male and female mice were exposed to cyclophosphamide via a single intraperitoneal (i.p.) injection at 200 mg/kg. Sperms and oocytes were collected at day 33 and day 10 respectively, for insemination and fertilization in medium supplemented with thymoquinone(1μM, 10μM and 100μM). The stages of fertilization, embryo division, morphological effects and fragmentation were examined and compared between groups, 24 hours post-fertilization. Thymoquinone supplementation improved fertilization rates, significantly reduced the percentage of defects blastomeres of Type C (p<0.001) and significantly decreased the percentage of embryo fragmentation Grade IV (>50%, p<0.05) following paternal and maternal exposures to cyclophosphamide. The good quality embryos of Type A and Grade I fragmentation were not observed in the group without thymoquinone supplementation. The findings of this study showed that thymoquinone is a suitable exogenous antioxidant for preserving fair-quality embryos which can result into full term pregnancy.